LTCC material with low dielectric constant, low loss and low thermal expansion coefficient, preparation method of LTCC material and electronic component

By adding CBS glass to cordierite ceramics as a sintering material, the problem of difficulty in sintering cordierite ceramics at low temperatures is solved, and the preparation of LTCC materials with low dielectric constant, low dielectric loss, and low thermal expansion coefficient is achieved, meeting the demand for high-performance materials of modern electronic components.

CN119874199APending Publication Date: 2025-04-25SHENZHEN SUNLORD ELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411869489.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to sinter cordierite ceramics at low temperatures, which makes it unable to meet the sintering temperature requirements of LTCC materials, affecting its application in electronic components.

Method used

By adding CBS glass to cordierite ceramics as a firing material, the sintering temperature is reduced, and the low-temperature sintering of cordierite ceramics is achieved, thereby preparing LTCC materials with low dielectric constant, low dielectric loss and low thermal expansion coefficient.

Benefits of technology

The low-temperature sintering of cordierite ceramics is achieved, which meets the demand for LTCC materials for low dielectric constant, low dielectric loss and low thermal expansion coefficient, and improves the overall performance and application applicability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874199A_ABST
    Figure CN119874199A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, in particular to a low-dielectric low-loss low-thermal-expansion-coefficient LTCC material, a preparation method thereof and an electronic component, and discloses the low-dielectric low-loss low-thermal-expansion-coefficient LTCC material which meets the requirement that the dielectric constant is 5.0-5.5; and / or a dielectric loss < 0.002; and / or a coefficient of thermal expansion of 4.0 to 5.2 ppm / K. According to the LTCC material with the low dielectric constant, the low loss and the low thermal expansion coefficient, by optimizing the components of the LTCC material, the LTCC material with the low dielectric constant, the low dielectric loss and the low thermal expansion coefficient is obtained, and the requirements of modern electronic components for high-performance materials are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional ceramic materials, and in particular to a low-dielectric, low-loss, low thermal expansion coefficient LTCC material, a preparation method thereof, and an electronic component. Background Art

[0002] Low Temperature Co-fired Ceramic (LTCC) technology is a new type of multi-layer substrate process technology, which is widely used in the production of electronic components in microwave communications, semiconductors, optoelectronics and other fields. It has the significant advantages of high integration and high performance.

[0003] In order to meet the process requirements of LTCC technology, LTCC materials usually need to have a lower sintering temperature (<900°C) to meet the co-firing requirements with high-conductivity metal conductors, and a lower dielectric constant to meet the dielectric loss. In addition, in order to improve the connection reliability between the surface-mounted chip and the LTCC substrate, the thermal expansion coefficient of the LTCC substrate material is required to be close to the thermal expansion coefficient of the silicon chip (about 3.5ppm / °C), otherwise the chip will generate thermal stress under reciprocating thermal cycles, causing the chip to be mismatched with the substrate and peel off from the substrate.

[0004] Cordierite has a low dielectric constant and thermal expansion coefficient, as well as good mechanical strength and electrical insulation properties, and is considered to be a dielectric material with great development prospects. However, due to the high sintering temperature of cordierite (>1300°C), it obviously cannot meet the sintering temperature requirements of LTCC substrates. Therefore, how to utilize the excellent dielectric properties and low thermal expansion coefficient of cordierite while making the sintering temperature meet the LTCC process requirements (below 900°C) has become a technical problem that needs to be solved in the application of cordierite in LTCC materials.

[0005] In view of this, the purpose of the present invention is to provide a new technical solution to solve the existing technical problems. Summary of the invention

[0006] The present application discloses a low-dielectric, low-loss, low thermal expansion coefficient LTCC material, a preparation method thereof, and an electronic component. The low-dielectric, low-loss, low thermal expansion coefficient LTCC material uses CBS glass material as a sintering aid material, reduces the sintering temperature of cordierite ceramics, and realizes low-temperature sintering of cordierite ceramics, thereby preparing a low-dielectric, low-loss, low thermal expansion coefficient LTCC material to meet the needs of modern electronic components for low-dielectric, low-loss, and low thermal expansion coefficient materials.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] The first purpose of the present application is to provide a low dielectric, low loss and low thermal expansion coefficient LTCC material that meets:

[0009] The dielectric constant is 5.0 to 5.5;

[0010] And\or dielectric loss <0.002;

[0011] And\or the thermal expansion coefficient is 4.0~5.2ppm / K.

[0012] In some specific embodiments, the LTCC material is obtained by sintering the following raw materials in parts by weight: a part of CBS glass, b part of cordierite glass-ceramics, c part of cordierite ceramics, d part of Al2O3, and e part of SiO2;

[0013] Among them, a is 30-50%, b is 0-10%, c is 30-50%, d is 5-10%, e is 2-5%, and a+b+c+d+e=100%.

[0014] In some specific embodiments, the CBS glass comprises the following raw materials in percentage by weight:

[0015] CaCO3: 1~3%, Al2O3: 1~5%, B2O3: 20~35%, SiO2: 60~75%.

[0016] In some specific embodiments, the cordierite glass-ceramics includes the following raw materials in percentage by weight:

[0017] MgO: 10~20%, Al2O3: 20~30%, SiO2: 45~55%.

[0018] In some specific embodiments, the cordierite ceramic comprises the following raw materials in a molar ratio:

[0019] MgO:Al2O3:SiO2 is 2:2:5.

[0020] In some specific embodiments, the LTCC material is obtained by mixing and sintering a part of CBS glass, b part of cordierite glass-ceramics, c part of cordierite ceramics, d part of Al2O3, and e part of SiO2, and includes the following components in percentage by mass:

[0021] SiO2: 50 to 75%, Al2O3: 15 to 33%, B2O3: 6 to 18%, MgO: 4 to 9%, CaO: 0.3 to 1%.

[0022] In some specific embodiments, after sintering, 75-90% of the physical phase of the LTCC material is cordierite phase, and 10-25% is α-alumina phase.

[0023] In some embodiments, the LTCC material can be sintered at 900°C.

[0024] The second object of the present application is to provide a method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material, comprising the following steps:

[0025] 1) In terms of mass fractions, a part of CBS glass, b part of cordierite glass-ceramics, c part of cordierite ceramics, d part of Al2O3, and e part of SiO2 are prepared; wherein a is 30-50%, b is 0-10%, c is 30-50%, d is 5-10%, and e is 2-5%, and a+b+c+d+e=100%;

[0026] 2) ball milling the ingredients in step 1) and mixing them evenly, and drying them;

[0027] 3) Add a binder to granulate, press into shape, and then sinter in an air atmosphere at 850-900°C to obtain a low dielectric, low loss, and low thermal expansion coefficient LTCC material.

[0028] The third object of the present application is to provide an electronic component, comprising the low dielectric, low loss, and low thermal expansion coefficient LTCC material described in the first object or the LTCC material prepared by the preparation method of the second object.

[0029] The beneficial effects of the present invention are:

[0030] The low-dielectric, low-loss, and low-thermal expansion coefficient LTCC material described in the present application has the properties of low dielectric constant, low dielectric loss, and low thermal expansion coefficient, and can meet the needs of modern electronic components for high-performance materials. By adding CBS glass as a sintering aid material to cordierite ceramics, the sintering temperature of cordierite ceramics is reduced, low-temperature sintering of cordierite ceramics is achieved, and co-firing with electrode materials can be achieved.

[0031] The preparation method described in the present application achieves complementarity and optimization of material properties by mixing CBS glass powder, cordierite glass-ceramic powder, cordierite ceramic powder, Al2O3 powder and SiO2 powder. The mixed raw materials can form a dense, pore-free material with good glass-ceramic compatibility during the sintering process, thereby improving the overall performance of the material; cordierite ceramics have a low dielectric constant, low dielectric loss, and low thermal expansion coefficient, while CBS ceramics can form a liquid phase at a relatively low temperature. The addition of CBS glass and cordierite glass-ceramics can reduce the sintering temperature, thereby achieving low-temperature sintering of cordierite materials, and then being applied to LTCC technology.

[0032] The electronic components described in the present application are made of LTCC materials and have the effects of low dielectric constant, low loss and low thermal expansion coefficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0034] Figure 1 is a SEM image of the LTCC material prepared in Example 6 of the present invention;

[0035] Figure 2 is a cross-sectional SEM image of the sintered comparative example 2 of the present invention;

[0036] Figure 3 is the XRD pattern of the LTCC material prepared in Example 6 of the present invention;

[0037] Figure 4 It is a schematic flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0038] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0039] As used herein, "and / or" includes the term of any and all combinations of one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.

[0040] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.

[0041] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.

[0042] The raw materials or reagents used in the embodiments of the present invention and the comparative examples are all purchased from mainstream manufacturers in the market. The manufacturer or concentration is not specified, and they are all analytically pure raw materials or reagents that can be routinely obtained. As long as the expected effect can be achieved, there is no particular restriction. The instruments and equipment used in the present embodiment are all purchased from major manufacturers in the market. As long as the expected effect can be achieved, there is no particular restriction. If specific techniques or conditions are not specified in the present embodiment, the techniques or conditions described in the literature in this area or according to the product specification are carried out.

[0043] Terminology explanation:

[0044] Cordierite ceramics: A ceramic material with cordierite (2MgO·2Al2O3·5SiO2) as the main crystal phase. It has excellent dielectric properties, but its sintering temperature is high and it cannot be directly applied to LTCC technology.

[0045] Dielectric constant (εr): It is a measure of a material's ability to store charge in an electric field and determines the frequency response characteristics of electronic components.

[0046] Dielectric loss: Energy loss caused by conductivity and polarization relaxation processes inside the material under the action of an electric field, affecting its energy efficiency and signal integrity.

[0047] Coefficient of thermal expansion: It is a physical quantity that characterizes the thermal expansion properties of an object, describing the degree to which the length, area, and volume of an object increase when heated.

[0048] PVA (Polyvinyl Alcohol): Polyvinyl alcohol, a commonly used adhesive.

[0049] D 50 : Refers to the particle size value when the cumulative distribution reaches 50% in the particle size distribution, which is a measure of the particle size distribution.

[0050] When currently LTCC devices are used on Si-based chips (3.5ppm / K), the thermal expansion coefficient needs to be as low as possible. The thermal expansion coefficient of most LTCC materials is between 7 and 9ppm / K. Cordierite has a relatively low dielectric constant and thermal expansion coefficient, and has good mechanical strength and electrical insulation properties. It is considered to be a dielectric material with great development prospects. However, due to the relatively high sintering temperature of cordierite (>1300°C), it obviously cannot meet the sintering temperature requirements of the LTCC substrate. In order to reduce the sintering temperature of cordierite ceramics to prepare a low-dielectric, low-loss, low-thermal expansion coefficient LTCC material, the present application provides a low-dielectric, low-loss, low-thermal expansion coefficient LTCC material, which satisfies:

[0051] The dielectric constant is 5.0 to 5.5;

[0052] And\or dielectric loss <0.002;

[0053] And\or the thermal expansion coefficient is 4.0~5.2ppm / K.

[0054] Specifically, the LTCC material meets the following requirements: a dielectric constant of 5.0 to 5.5 and a dielectric loss of less than 0.002.

[0055] Or the LTCC material meets the following requirements: dielectric constant of 5.0 to 5.5, thermal expansion coefficient of 4.0 to 5.2 ppm / K.

[0056] Or the LTCC material meets the following requirements: dielectric constant of 5.0 to 5.5, dielectric loss < 0.002, and thermal expansion coefficient of 4.0 to 5.2 ppm / K.

[0057] The LTCC material is obtained by sintering the following raw materials in parts by weight: a part of CBS glass, b part of cordierite glass-ceramics, c part of cordierite ceramics, d part of Al2O3, and e part of SiO2;

[0058] Among them, a is 30-50%, b is 0-10%, c is 30-50%, d is 5-10%, e is 2-5%, and a+b+c+d+e=100%.

[0059] Since CBS glass has a low melting point and low dielectric constant, cordierite ceramics are used as the main crystal phase, and CBS glass is used to assist in sintering, which can reduce the sintering temperature of cordierite ceramics; but since the loss of CBS glass is relatively large, it is necessary to increase the content of cordierite phase as much as possible while achieving low-temperature sintering, and cordierite microcrystalline glass itself can sinter at 900°C to precipitate cordierite phase, so adding cordierite microcrystalline glass can help reduce the amount of CBS glass. A small amount of Al2O3 and SiO2 can be used as filling phases to adjust dielectric properties. The above-mentioned LTCC materials can meet the requirements of low dielectric constant, low dielectric loss and low thermal expansion coefficient while meeting the low-temperature sintering requirements at 900°C.

[0060] The mass fraction of CBS glass is 30-50%, for example, it can be any value of 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49% and 50%. The mass fraction of CBS glass is 30-50% (including the endpoint values), which can reduce the sintering temperature and promote the densification of the material. The mass fraction of CBS glass material is less than 30%, which has limited effect on reducing the sintering temperature and cannot achieve sufficient sintering-aiding effect. The mass fraction of CBS glass material is higher than 50%, which may lead to a decrease in the dielectric properties of the material.

[0061] The mass fraction of cordierite glass-ceramics is 0-10%, for example, it can be any value among 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% and 10%; cordierite glass-ceramics can precipitate cordierite phase when sintered at 900°C, and the mass fraction of cordierite glass-ceramics is 0-10% (including the endpoint values), which can increase the cordierite content while controlling the amount of CBS glass material.

[0062] The mass fraction of cordierite ceramic is 30-50%, for example, it can be any value among 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49% and 50%. The mass fraction of cordierite ceramic material is 30-50% (including the endpoint values), which can ensure that the material has good dielectric properties and low thermal expansion coefficient. If the mass fraction of cordierite ceramic is less than 30%, the material may not achieve an ideal thermal expansion coefficient. If the mass fraction of cordierite ceramic is higher than 50%, the material sintering temperature may be greater than 900°C, which is not conducive to the low-temperature sintering and densification of the material.

[0063] The mass fraction of Al2O3 is 5-10%, for example, it can be any value among 5%, 6%, 7%, 8%, 9% and 10%; the mass fraction of Al2O3 is 5-10% (including the endpoint values), which can improve the mechanical strength and hardness of the material, and also participate in adjusting the dielectric constant; the mass fraction of Al2O3 is less than 5%, the effect is not obvious; the mass fraction of Al2O3 is more than 10%, it may hinder the effective combination of other components.

[0064] The mass fraction of SiO2 is 2-5%, for example, it can be any value among 2%, 3%, 4% and 5%; the mass fraction of SiO2 is 2-5% (including the endpoint values), as a filling phase, it can improve the mechanical properties and thermal stability of the material, and also participate in improving the dielectric properties; the mass fraction of SiO2 is less than 2%, the effect is not obvious; the mass fraction of SiO2 is more than 5% and it may also hinder the effective combination of other components.

[0065] Specifically, CBS glass includes the following raw materials in percentage by weight:

[0066] CaCO3: 1~3%, Al2O3: 1~5%, B2O3: 20~35%, SiO2: 60~75%.

[0067] In CBS glass, SiO2 and B2O3 are the glass network structures, CaO and B2O3 play the role of lowering the melting point, and Al2O3 plays the role of regulating and improving the physical and chemical properties of the glass.

[0068] The preparation process of CBS glass is as follows: CaCO3, Al2O3, B2O3, and SiO2 are weighed according to the raw material composition ratio by mass percentage, each raw material is mixed evenly by wet ball milling, and then put into a crucible after drying, and melted at 1500-1600°C for 2-3h to form glass liquid, and then quenched by deionized water, and then dried and ground to obtain the CBS glass powder; the particle size of the obtained CBS glass powder is controlled to be 2μm<D 50 <3μm.

[0069] In some specific embodiments, the cordierite glass-ceramics includes the following raw materials in percentage by weight:

[0070] MgO: 10~20%, Al2O3: 20~30%, SiO2: 45~55%.

[0071] In cordierite glass-ceramics, MgO plays a role in lowering the melting point, SiO2 provides the main network structure of the glass, and Al2O3 plays a role in regulating and improving the physical and chemical properties of the glass.

[0072] Cordierite glass-ceramics can precipitate cordierite phase at 900°C. Adding cordierite glass-ceramics for co-firing can reduce the content of CBS glass in the raw materials, thereby reducing the dielectric loss of the LTCC material after sintering and ensuring the dielectric properties of the material.

[0073] The preparation process of cordierite glass-ceramics is as follows: corresponding MgO, Al2O3, and SiO2 are weighed according to the raw material composition ratio by mass percentage, each raw material is mixed evenly by wet ball milling, and then loaded into a crucible after drying, and melted at 1500-1600°C for 2-3h to form glass liquid, and quenched by deionized water, and then dried and ground to obtain the cordierite glass-ceramics powder; the particle size of the obtained cordierite glass-ceramics powder is controlled to be 2μm<D 50 <3μm.

[0074] In some specific embodiments, the cordierite ceramic comprises the following raw materials in a molar ratio:

[0075] MgO:Al2O3:SiO2 is 2:2:5.

[0076] In cordierite ceramics, MgO plays a role in lowering the melting point, SiO2 provides the main network structure of the ceramics, and Al2O3 plays a role in regulating and improving the physical and chemical properties of the ceramics.

[0077] The preparation process of cordierite ceramics is as follows: the ingredients are weighed according to the molar ratio of MgO:Al2O3:SiO2 of 2:2:5, the raw materials are mixed evenly by wet ball milling, and then dried, crushed and sieved, calcined at 1100-1200°C for 2h, and then planetary ball milled to obtain the cordierite ceramic powder. The particle size of the obtained cordierite ceramic powder is controlled to be 0.5μm<D 50 <2μm.

[0078] Therefore, the above-mentioned LTCC material is obtained by mixing ceramic phase material, glass phase material, etc., and then ball milling and sintering.

[0079] Specifically, the LTCC material is obtained by mixing and sintering a part of CBS glass, b part of cordierite glass-ceramics, c part of cordierite ceramics, d part of Al2O3, and e part of SiO2, and includes the following components in percentage by mass:

[0080] SiO2: 50 to 75%, Al2O3: 15 to 33%, B2O3: 6 to 18%, MgO: 4 to 9%, CaO: 0.3 to 1%.

[0081] In a certain embodiment, the LTCC material includes the following components in percentage by weight:

[0082] SiO2: 50%, Al2O3: 33%, B2O3: 7.7%, MgO: 9%, CaO: 0.3%.

[0083] Alternatively, the LTCC material comprises the following components in percentage by weight:

[0084] SiO2: 75%, Al2O3: 14%, B2O3: 6%, MgO: 4%, CaO: 1%.

[0085] Alternatively, the LTCC material comprises the following components in percentage by weight:

[0086] SiO2: 60%, Al2O3: 15%, B2O3: 18%, MgO: 6%, CaO: 1%.

[0087] Alternatively, the LTCC material comprises the following components in percentage by weight:

[0088] SiO2: 58%, Al2O3: 23%, B2O3: 12%, MgO: 6.35%, CaO: 0.65%.

[0089] Specifically, the present application adjusts the raw material composition of the LTCC material so that the mass percentage of the components of the prepared LTCC material is controlled within the range of:

[0090] SiO2: 50 to 75%, Al2O3: 15 to 33%, B2O3: 6 to 18%, MgO: 4 to 9%, CaO: 0.3 to 1%.

[0091] Specifically, among the physical phases of the LTCC material after sintering, 75-90% is the cordierite phase, and 10-25% is the α-alumina phase.

[0092] In some embodiments, the LTCC material may be sintered at 900°C.

[0093] Therefore, the LTCC material can achieve dense sintering at 900° C. and has properties of a dielectric constant between 5.0 and 5.5, a dielectric loss less than or equal to 0.002, and a thermal expansion coefficient between 4.0 ppm / K and 5.2 ppm / K.

[0094] It can be understood that the LTCC material of the present application is a composite sintered material of a ceramic phase material (cordierite ceramic) and a glass phase material (CBS glass and cordierite glass-ceramics), wherein the glass phase material contains a material that can reduce the sintering temperature of the low-temperature co-fired ceramic material and regulate the dielectric constant.

[0095] The embodiment of the present invention also provides a method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material, comprising the following steps:

[0096] 1) In terms of mass fraction, a part of CBS glass, b part of cordierite glass-ceramics, c part of cordierite ceramics, d part of Al2O3, and e part of SiO2 are prepared.

[0097] Wherein, a is 30-50%, b is 0-10%, c is 30-50%, d is 5-10%, e is 2-5%, and a+b+c+d+e=100%;

[0098] 2) ball milling the ingredients in step 1) and mixing them evenly, and drying them;

[0099] 3) Add a binder to granulate, press into shape, and then sinter in an air atmosphere at 850-900°C to obtain a low dielectric, low loss, and low thermal expansion coefficient LTCC material.

[0100] The raw material components of the CBS glass in the embodiment of the present invention are calculated by mass fraction: 1-3% CaCO3, 1-5% Al2O3, 20-35% B2O3, and 60-75% SiO2.

[0101] The raw material components of the cordierite glass-ceramics in the embodiment of the present invention are calculated by mass fraction: 10-20% MgO, 20-30% Al2O3, and 45-55% SiO2.

[0102] In step 2), water is used as the solvent and the ball milling is performed by planetary ball milling. The ingredients are subjected to planetary ball milling for 6 to 12 hours, and the slurry particle size is controlled to be D 50 0.5~5μm.

[0103] In step 3), a debinding operation is performed after compression molding and before sintering; specifically, debinding is performed at 450-500° C. for 2-3 hours, and then sintering is performed in an air atmosphere at 850-900° C. for 0.5-2 hours to obtain the LTCC material.

[0104] Therefore, in the raw material composition of LTCC materials, the ceramic phase material (cordierite ceramic) provides excellent electrical and thermal properties, while the glass phase material (CBS glass and cordierite glass-ceramics) reduces the sintering temperature, promotes the densification of the material, and improves the processing performance and mechanical strength. The synergistic effect of the ceramic phase material and the glass phase material enables the LTCC material to meet the low-temperature sintering requirements at 900°C while maintaining a low dielectric constant, low loss and low thermal expansion coefficient.

[0105] In addition, the present application also provides an electronic component, including the above-mentioned low-dielectric, low-loss, low-thermal expansion coefficient LTCC material; the electronic component can be used in AI servers, computers, collections or other electronic components containing low-dielectric, low-loss, low-thermal expansion coefficient LTCC materials.

[0106] The following is a further description of a low dielectric, low loss, low thermal expansion coefficient LTCC material and electronic components of the present invention in combination with specific preparation examples, embodiments, and comparative examples:

[0107] Preparation Example 1

[0108] The preparation method of CBS glass comprises the following steps:

[0109] The raw material composition ratio by mass percentage is CaCO3 1%, Al2O3 1%, B2O3 23%, SiO2 75%, which are called the corresponding raw materials;

[0110] The raw materials were mixed evenly by wet ball milling, dried and put into a crucible, melted at 1600℃ for 3h to form glass liquid, quenched by deionized water, and then dried and ground to obtain CBS glass powder with a particle size of 2μm<D 50 <3μm.

[0111] Preparation Example 2

[0112] The preparation method of CBS glass comprises the following steps:

[0113] The raw material composition ratio by mass percentage is CaCO3 3%, Al2O3 5%, B2O3 20%, SiO2 72%, which are called the corresponding raw materials;

[0114] The raw materials were mixed evenly by wet ball milling, dried and put into a crucible, melted at 1500℃ for 2.5h to form glass liquid, quenched by deionized water, and then dried and ground to obtain CBS glass powder with a particle size of 2μm<D 50 <3μm.

[0115] Preparation Example 3

[0116] The preparation method of CBS glass comprises the following steps:

[0117] The raw material composition ratio by mass percentage is CaCO3 2%, Al2O3 3%, B2O3 35%, SiO2 60%, which are called the corresponding raw materials;

[0118] The raw materials were mixed evenly by wet ball milling, dried and put into a crucible, melted at 1500℃ for 2h to form glass liquid, quenched by deionized water, and then dried and ground to obtain CBS glass powder with a particle size of 2μm<D 50 <3μm.

[0119] Preparation Example 4

[0120] A method for preparing cordierite glass-ceramics comprises the following steps:

[0121] The raw material composition ratio by mass percentage is 15% MgO, 30% Al2O3, and 55% SiO2. The raw materials are mixed evenly by wet ball milling, dried, and loaded into a crucible, melted at 1600°C for 3 hours to form a glass liquid, quenched by deionized water, and then dried and ground to obtain the cordierite microcrystalline glass powder, with a particle size controlled at 2μm<D 50 <3μm.

[0122] Preparation Example 5

[0123] A method for preparing cordierite glass-ceramics comprises the following steps:

[0124] The raw material composition ratio by mass percentage is 20% MgO, 30% Al2O3, and 50% SiO2. The raw materials are mixed evenly by wet ball milling, dried, and loaded into a crucible, melted at 1500°C for 2.5 hours to form a glass liquid, quenched by deionized water, and then dried and ground to obtain the cordierite microcrystalline glass powder, with a particle size controlled at 2μm<D 50 <3μm.

[0125] Preparation Example 6

[0126] A method for preparing cordierite glass-ceramics comprises the following steps:

[0127] The raw material composition ratio by mass percentage is 20% MgO, 25% Al2O3, and 55% SiO2. The raw materials are mixed evenly by wet ball milling, dried, and loaded into a crucible, melted at 1600°C for 3 hours to form a glass liquid, quenched by deionized water, and then dried and ground to obtain the cordierite microcrystalline glass powder, with a particle size controlled at 2μm<D 50 <3μm.

[0128] Preparation Example 7

[0129] A method for preparing cordierite ceramics comprises the following steps:

[0130] The ingredients are weighed according to the molar ratio of MgO:Al2O3:SiO2 of 2:2:5, and the raw materials are mixed evenly by wet ball milling, and then dried, crushed and sieved, calcined at 1100°C for 2h, and then planetary ball milled to obtain the cordierite ceramic powder. The particle size of the obtained cordierite ceramic powder is controlled at 0.5μm<D50<2μm.

[0131] Example 1

[0132] A method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material is carried out according to the following steps:

[0133] 1) In terms of mass fractions, a part of CBS glass (from Preparation Example 1), b part of cordierite glass-ceramics (from Preparation Example 4), c part of cordierite ceramic (from Preparation Example 7), d part of Al2O3, and e part of SiO2 are prepared;

[0134] Among them, a is 50%, b is 0%, c is 38%, d is 10%, and e is 2%;

[0135] 2) The raw materials in step 1) were ball milled for 6 hours, and the slurry particle size was controlled to D 50 The particle size is 3 μm, and LTCC ceramic powder is obtained after drying.

[0136] 3) PVA adhesive is added to the LTCC ceramic powder obtained in step 2) to make granules, and after pressing and molding, the granules are debonded at 450° C. for 2 hours, and then sintered at 850° C. in air atmosphere for 2 hours to obtain a low dielectric, low loss, and low thermal expansion coefficient LTCC material.

[0137] Example 2

[0138] A method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material is carried out according to the following steps:

[0139] 1) In terms of mass fractions, a part of CBS glass (from Preparation Example 2), b part of cordierite glass-ceramics (from Preparation Example 5), c part of cordierite ceramic (from Preparation Example 7), d part of Al2O3, and e part of SiO2 are prepared;

[0140] Among them, a is 45%, b is 5%, c is 38%, d is 10%, and e is 2%;

[0141] 2) The raw materials in step 1) were ball milled for 6 hours, and the slurry particle size was controlled to D 50 The particle size is 3 μm, and LTCC ceramic powder is obtained after drying.

[0142] 3) PVA adhesive is added to the LTCC ceramic powder obtained in step 2) to make granules, and after pressing and molding, the granules are debonded at 450° C. for 2 hours, and then sintered at 900° C. in air atmosphere for 2 hours to obtain a low dielectric, low loss, and low thermal expansion coefficient LTCC material.

[0143] Example 3

[0144] A method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material is carried out according to the following steps:

[0145] 1) In terms of mass fractions, a part of CBS glass (from Preparation Example 3), b part of cordierite glass-ceramics (from Preparation Example 6), c part of cordierite ceramic (from Preparation Example 7), d part of Al2O3, and e part of SiO2 are prepared;

[0146] Among them, a is 40%, b is 5%, c is 45%, d is 5%, and e is 5%;

[0147] 2) The raw materials in step 1) were ball milled for 6 hours, and the slurry particle size was controlled to D 50 The particle size is 3 μm, and LTCC ceramic powder is obtained after drying.

[0148] 3) PVA adhesive is added to the LTCC ceramic powder obtained in step 2) to make granules, and after pressing and molding, the granules are debonded at 450° C. for 2 hours, and then sintered at 900° C. in air atmosphere for 2 hours to obtain a low dielectric, low loss, and low thermal expansion coefficient LTCC material.

[0149] Example 4

[0150] A method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material is carried out according to the following steps:

[0151] 1) In terms of mass fractions, a part of CBS glass (from Preparation Example 1), b part of cordierite glass-ceramics (from Preparation Example 4), c part of cordierite ceramic (from Preparation Example 7), d part of Al2O3, and e part of SiO2 are prepared;

[0152] Among them, a is 40%, b is 10%, c is 40%, d is 5%, and e is 5%;

[0153] 2) The raw materials in step 1) were ball milled for 12 hours, and the slurry particle size was controlled to D 50 The particle size is 0.5 μm, and LTCC ceramic powder is obtained after drying.

[0154] 3) PVA adhesive is added to the LTCC ceramic powder obtained in step 2) to make granules, and after pressing and molding, the granules are debonded at 500° C. for 4 hours, and then sintered at 900° C. in air atmosphere for 2 hours to obtain a low dielectric, low loss, and low thermal expansion coefficient LTCC material.

[0155] Example 5

[0156] A method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material is carried out according to the following steps:

[0157] 1) In terms of mass fractions, a part of CBS glass (from Preparation Example 2), b part of cordierite glass-ceramics (from Preparation Example 5), c part of cordierite ceramic (from Preparation Example 7), d part of Al2O3, and e part of SiO2 are prepared;

[0158] Among them, a is 35%, b is 10%, c is 45%, d is 5%, and e is 5%;

[0159] 2) The raw materials in step 1) were ball milled for 12 hours, and the slurry particle size was controlled to D 50 The particle size is 0.5 μm, and LTCC ceramic powder is obtained after drying.

[0160] 3) PVA adhesive is added to the LTCC ceramic powder obtained in step 2) to make granules, and after pressing and molding, the granules are debonded at 500° C. for 4 hours, and then sintered at 900° C. in air atmosphere for 2 hours to obtain a low dielectric, low loss, and low thermal expansion coefficient LTCC material.

[0161] Example 6

[0162] A method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material is carried out according to the following steps:

[0163] 1) In terms of mass fractions, a part of CBS glass (from Preparation Example 3), b part of cordierite glass-ceramics (from Preparation Example 6), c part of cordierite ceramic (from Preparation Example 7), d part of Al2O3, and e part of SiO2 are prepared;

[0164] Among them, a is 30%, b is 10%, c is 50%, d is 5%, and e is 5%;

[0165] 2) The raw materials in step 1) were ball milled for 12 hours, and the slurry particle size was controlled to D 50 The particle size is 0.5 μm, and LTCC ceramic powder is obtained after drying.

[0166] 3) PVA adhesive is added to the LTCC ceramic powder obtained in step 2) to make granules, and after pressing and molding, the granules are debonded at 500° C. for 4 hours, and then sintered at 900° C. in air atmosphere for 2 hours to obtain a low dielectric, low loss, and low thermal expansion coefficient LTCC material.

[0167] Comparative Example 1

[0168] A method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material is carried out according to the following steps:

[0169] 1) In terms of mass fractions, a part of CBS glass (from Preparation Example 3), c parts of cordierite ceramic (from Preparation Example 7), d parts of Al2O3, and e parts of SiO2 are prepared;

[0170] Among them, a is 65%, c is 25%, d is 10%, and e is 0%;

[0171] 2) The raw materials in step 1) were ball milled for 12 hours, and the slurry particle size was controlled to D 50 The particle size is 0.5 μm, and LTCC ceramic powder is obtained after drying.

[0172] 3) PVA binder is added to the LTCC ceramic powder obtained in step 2) to form granules, and after pressing and molding, the granules are debonded at 500° C. for 4 hours, and then sintered at 900° C. in air atmosphere for 2 hours to obtain the LTCC material.

[0173] Comparative Example 2

[0174] A method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material is carried out according to the following steps:

[0175] 1) In terms of mass fractions, a part of CBS glass (from Preparation Example 1), c parts of cordierite ceramic (from Preparation Example 7), d parts of Al2O3, and e parts of SiO2 are prepared;

[0176] Among them, a is 20%, c is 65%, d is 10%, and e is 5%;

[0177] 2) The raw materials in step 1) were ball milled for 6 hours, and the slurry particle size was controlled to D 50 The particle size is 3 μm, and LTCC ceramic powder is obtained after drying.

[0178] 3) PVA adhesive is added to the LTCC ceramic powder obtained in step 2) to form granules, and after compression molding, the granules are debonded at 450° C. for 2 h, and then sintered at 850° C. in an air atmosphere for 2 h to obtain the LTCC material.

[0179] Comparative Example 3

[0180] A method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material is carried out according to the following steps:

[0181] 1) In parts by mass, c parts of cordierite ceramic (from Preparation Example 7), d parts of Al2O3, and e parts of SiO2 are prepared;

[0182] Among them, c is 38%, d is 47%, and e is 15%;

[0183] 2) The raw materials in step 1) were ball milled for 6 hours, and the slurry particle size was controlled to D 50 The particle size is 3 μm, and then dried to obtain a powder material.

[0184] 3) PVA binder is added to the powder material obtained in step 2) to form granules, and after compression molding, the granules are debonded at 450° C. for 2 h, and then sintered at 850° C. in air atmosphere for 2 h.

[0185] Comparative Example 4

[0186] A method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material is carried out according to the following steps:

[0187] 1) In terms of mass fractions, a part of CBS glass (from Preparation Example 1), d part of Al2O3, and e part of SiO2 are prepared;

[0188] Among them, a is 50%, d is 35%, and e is 15%;

[0189] 2) The raw materials in step 1) were ball milled for 6 hours, and the slurry particle size was controlled to D50 The particle size is 3 μm, and LTCC ceramic powder is obtained after drying.

[0190] 3) PVA adhesive is added to the LTCC ceramic powder obtained in step 2) to form granules, and after compression molding, the granules are debonded at 450° C. for 2 h, and then sintered at 850° C. in an air atmosphere for 2 h to obtain the LTCC material.

[0191] The low dielectric constant, dielectric loss and thermal expansion coefficient of the low-loss LTCC materials prepared in Examples 1-6 and Comparative Examples 1-4 were tested for dielectric constant, dielectric loss and thermal expansion coefficient. The relevant results are summarized in Table 1:

[0192] Among them: dielectric constant and dielectric loss are tested by using dielectric spectrometer; thermal expansion coefficient is tested by using thermal expansion coefficient tester.

[0193] Table 1

[0194]

[0195] It can be seen from Table 1 that the low-dielectric, low-loss, low thermal expansion coefficient LTCC materials prepared in Examples 1-6 have low dielectric constant (5.0-5.5), low dielectric loss (≤0.002) and low thermal expansion coefficient (4.0-5.2ppm / k). At the same time, the low-dielectric, low-loss, low thermal expansion coefficient LTCC materials prepared in Examples 1-6 can be sintered densely at 900°C, and are suitable for use in LTCC devices that require low dielectric constant, low loss and low thermal expansion coefficient.

[0196] In comparative example 1, a small amount of CBS glass is used for co-firing with cordierite ceramics. Although the dielectric constant remains at a low level, the dielectric loss increases significantly, reaching 0.004. The dielectric loss is large, the density is poor, and it does not have an application basis.

[0197] In Comparative Example 2, a large amount of CBS glass is used for co-firing with cordierite ceramics, and the CBS glass content is too high. Although low-temperature sintering can be achieved, the loss of CBS glass itself is much greater than that of cordierite ceramics, so the dielectric loss of Comparative Example 2 is also relatively large. At the same time, the cordierite ceramic content in Comparative Example 2 is low, and the thermal expansion coefficient reaches 6.5ppm / K, and the thermal expansion coefficient advantage is not obvious.

[0198] In Comparative Example 3, only cordierite ceramics, Al2O3 powder and SiO2 powder were added for sintering. Since the sintering temperature of cordierite is greater than 1300°C, no CBS glass was added to assist sintering, so low-temperature sintering could not be achieved and ceramics could not be formed in an air atmosphere at 850°C.

[0199] In Comparative Example 4, only CBS glass, Al2O3 powder and SiO2 powder were added for sintering. Although low-temperature sintering can be achieved, the thermal expansion coefficient of the LTCC material after sintering is relatively high, reaching 7.5ppm / K, because cordierite ceramics are not added, which has no obvious advantages. At the same time, the loss of CBS glass itself is relatively large, so the dielectric loss of Comparative Example 4 is also relatively large.

[0200] Figure 1 The surface morphology of the low dielectric, low loss and low thermal expansion coefficient LTCC material prepared in Example 6 under a scanning electron microscope is shown. Figure 1 It can be seen that the material is sintered densely, has no pores, and has good glass-ceramic mutuality. It also shows that by adding CBS glass and cordierite glass-ceramics, low-temperature sintering of cordierite ceramic materials can be achieved, and then co-firing with electrode materials can be achieved.

[0201] Figure 2 The cross-sectional SEM picture of comparative example 1 is shown. The microscopic morphology has many holes and is not dense. This is because the CBS glass content in comparative example 1 is too low to provide sufficient sintering aid effect. After sintering at 900°C, there are still a large number of holes.

[0202] Figure 3 The XRD pattern of the LTCC material prepared in Example 6 is shown. Figure 2 It can be seen that the main phases of the material after sintering are cordierite phase and α-alumina phase. The main crystal phase cordierite has excellent dielectric properties and low thermal expansion coefficient, which is the key to the LTCC material having low dielectric constant, low dielectric loss and low thermal expansion coefficient.

[0203] The low dielectric, low loss, and low thermal expansion coefficient LTCC materials prepared in Examples 1-6 and Comparative Examples 1-4 were subjected to chemical composition testing (for example, testing by inductively coupled plasma mass spectrometry), and Table 2 was obtained:

[0204] Table 2

[0205]

[0206] As can be seen from Table 2, the mass percentages of SiO2, Al2O3, B2O3, MgO and CaO in the low dielectric, low loss and low thermal expansion coefficient LTCC materials prepared in Examples 1-6 all meet the following requirements: SiO2: 50-75%, Al2O3: 15-33%, B2O3: 6-18%, MgO: 4-9% and CaO: 0.3-1%. However, the mass percentages of SiO2, Al2O3, B2O3, MgO and CaO in the materials prepared in Comparative Examples 1-4 do not meet the following requirements: SiO2: 50-75%, Al2O3: 15-33%, B2O3: 6-18%, MgO: 4-9% and CaO: 0.3-1%.

[0207] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A low dielectric, low loss, low thermal expansion coefficient LTCC material, characterized in that: satisfy: The dielectric constant is 5.0 to 5.5; And\or dielectric loss <0.002; And\or the thermal expansion coefficient is 4.0~5.2ppm / K.

2. The low dielectric, low loss, low thermal expansion coefficient LTCC material according to claim 1, characterized in that: The LTCC material is obtained by sintering the following raw materials in parts by weight: a part of CBS glass, b part of cordierite glass-ceramics, c part of cordierite ceramics, d part of Al2O3, and e part of SiO2; Among them, a is 30-50%, b is 0-10%, c is 30-50%, d is 5-10%, e is 2-5%, and a+b+c+d+e=100%.

3. The low dielectric, low loss, low thermal expansion coefficient LTCC material according to claim 2, characterized in that: The CBS glass comprises the following raw materials in percentage by mass: CaCO3: 1~3%, Al2O3: 1~5%, B2O3: 20~35%, SiO2: 60~75%.

4. The low dielectric, low loss, low thermal expansion coefficient LTCC material according to claim 2, characterized in that: The cordierite glass-ceramics comprises the following raw materials in percentage by mass: MgO: 10~20%, Al2O3: 20~30%, SiO2: 45~55%.

5. The low dielectric, low loss, low thermal expansion coefficient LTCC material according to claim 2, characterized in that: The cordierite ceramic comprises the following raw materials in a molar ratio: MgO:Al2O3:SiO2 is 2:2:

5.

6. The low dielectric, low loss, low thermal expansion coefficient LTCC material according to claim 2, characterized in that: The LTCC material is obtained by mixing and sintering a part of CBS glass, b part of cordierite glass-ceramics, c part of cordierite ceramics, d part of Al2O3, and e part of SiO2, and includes the following components in percentage by mass: SiO2: 50 to 75%, Al2O3: 15 to 33%, B2O3: 6 to 18%, MgO: 4 to 9%, CaO: 0.3 to 1%.

7. The low dielectric, low loss, low thermal expansion coefficient LTCC material according to claim 1, characterized in that: After sintering, 75-90% of the physical phases of the LTCC material are cordierite phases, and 10-25% are α-alumina phases.

8. A low dielectric, low loss, low thermal expansion coefficient LTCC material according to any one of claims 1 to 6, characterized in that: The LTCC material may be sintered at 900°C.

9. A method for preparing a low dielectric, low loss, and low thermal expansion coefficient LTCC material, characterized in that: The steps include: 1) In terms of mass fractions, a part of CBS glass, b part of cordierite glass-ceramics, c part of cordierite ceramics, d part of Al2O3, and e part of SiO2 are prepared; wherein a is 30-50%, b is 0-10%, c is 30-50%, d is 5-10%, and e is 2-5%, and a+b+c+d+e=100%; 2) ball milling the raw materials in step 1), mixing them uniformly, and drying them; 3) Add a binder to granulate, press into shape, and then sinter in an air atmosphere at 850-900°C to obtain a low dielectric, low loss, and low thermal expansion coefficient LTCC material.

10. An electronic component, characterized in that: The invention comprises the LTCC material according to any one of claims 1 to 8 or the LTCC material prepared by the preparation method according to claim 9.